2015
DOI: 10.1117/12.2079667
|View full text |Cite
|
Sign up to set email alerts
|

Surface-enhanced Brillouin scattering in a vicinity of plasmonic gold nanostructures

Abstract: Brillouin spectroscopy is a powerful tool for non-invasive elasticity-specific optical imaging. We report an observation of enhancements of Brillouin scattering from liquid samples in the presence of gold nanostructures. These enhancements are attributed to surface plasmons generated by nanostructures and are found to be dependent on the nanostructures' architecture (i.e. their sizes and aspect ratios). These observations suggest that plasmonic nanostructures composed of nanodisk arrays can provide a platform … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…Thus, to be employed as a source of OFCs, the intensity of the optical BLS modes has to be increased. It has recently been shown that the strength of the interaction of light with singlefrequency ultrasound is increased by using plasmonic nanostructures such as plasmonic grating and NAs [22,23]. Therefore, we capitalise on the previous results and demonstrate that the intensity of all BLS modes in the spectrum can be increased by using an ultra-small, singleelement plasmonic NA.…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…Thus, to be employed as a source of OFCs, the intensity of the optical BLS modes has to be increased. It has recently been shown that the strength of the interaction of light with singlefrequency ultrasound is increased by using plasmonic nanostructures such as plasmonic grating and NAs [22,23]. Therefore, we capitalise on the previous results and demonstrate that the intensity of all BLS modes in the spectrum can be increased by using an ultra-small, singleelement plasmonic NA.…”
Section: Introductionmentioning
confidence: 69%
“…The number of spectral lines obtained with the proposed OFC source is higher as compared with discrete spectra that may be produced by means a cascade of NL-optical four-wave mixing processes in a tapered NA [13]. However, the footprint of the proposed source is much smaller than that of tapered NAs and similar plasmonic nanostructures such as subwavelength gratings [22]. Furthermore, we have shown that the spacing between the lines of the spectrum synthesised from ultrasound can be controlled at will by changing the frequency and intensity of incident ultrasound or by controlling the NL acoustic parameter of the liquid.…”
Section: Discussionmentioning
confidence: 95%
“…It should be noted that, although water, urea, creatinine and uric acid are detectable by using conventional Raman scattering spectroscopy, the detection of Albumin protein in urine is very challenging due to low detection sensitivity of this technique to albumin concentration in urine [35] even in proteinuric samples. Therefore, there have been attempts to boost Raman signal by means of SERS spectroscopy [38,39], as well as our efforts to boost Brillouin light scattering signal using surface plasmon enhancement [40][41][42][43]. Each method of this study will give a valuable knowledge and full contribution to the aim and task of our study.…”
Section: Discussionmentioning
confidence: 99%
“…The recent advances in theory and application of phononic FCs [ 9 , 14 , 15 ] are discussed in detail in Section 4 . In Section 5 , we review FCs obtained using the Brillouin light scattering effect [ 16 , 17 , 18 ], and we also demonstrate the possibility of increasing the amplitude of spectral peaks in the comb spectra by means of plasmonic resonant effects supported by metal nanostructures [ 19 , 20 ]. The discussion of the novel approaches to the generation of AFCs continues in Section 6 and Section 7 , where we review the recent advances in the fields of AFC generated using oscillations of gas bubbles in liquids [ 21 , 22 ] and vibrations of liquid drops [ 23 , 24 ], respectively.…”
Section: Introductionmentioning
confidence: 99%